1988
DOI: 10.1111/j.1151-2916.1988.tb07541.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Relationships in the Silicon Carbide‐Aluminum Nitride System

Abstract: Phase relationships in the SIC-AIN system were determined by analytical electron microscopy of local equilibria among adjacent phases in hot-pressed samples and in diffusion couples. At 2100" to 2300"C, a 4H-2H equilibrium exists, the 4H field extending from =2 mol% AlN to an upper limit of 11 to 14 mol% AIN. The wurtzite-type 2H (6) solid solution extends from an impurity-sensitive lower limit of 17 to 24 mol% AIN up to 100 mol% AIN. Semiquantitative Auger electron spectroscopy and energy dispersive X-ray spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(103 citation statements)
references
References 8 publications
9
92
0
2
Order By: Relevance
“…8, and compared with the experiment-based miscibility gap of Zangvil and Ruh. 10 The lower calculated curve (shown in blue online) was calculated with the weighted CE-fit described above. The upper dot-dashed-curve (shown in red online) was calculated with a CE-fit that only included fDE < 0:10 eVg.…”
Section: Sic-innmentioning
confidence: 99%
See 1 more Smart Citation
“…8, and compared with the experiment-based miscibility gap of Zangvil and Ruh. 10 The lower calculated curve (shown in blue online) was calculated with the weighted CE-fit described above. The upper dot-dashed-curve (shown in red online) was calculated with a CE-fit that only included fDE < 0:10 eVg.…”
Section: Sic-innmentioning
confidence: 99%
“…10,11 In spite of an apparently strong tendency for immiscibility it is possible to synthesize wurtzite-structure solid solutions (SiC) 1ÀX (AlN) X as thin films or single crystals of arbitrary bulk composition, X (Refs. 1, 2 and 9).…”
Section: Introductionmentioning
confidence: 99%
“…The value of 3.2376 g/cm 3 was used as a theoretical density of the composite (SiC: AlN = 50:50 in mol).…”
Section: Analysis Of Sic-aln Compositesmentioning
confidence: 99%
“…Ruh 2) and Zangvil 3) presented tentative phase diagrams in SiC-AlN systems, and reported that SiC and AlN phases formed solid solutions in wide compositional ranges (SiC/10-90 mol% AlN, above 1900°C) because of the similarity of SiC and AlN in the crystallographic structure (2H phase). Therefore, if homogeneous SiC-AlN solid solutions can be obtained, the composites are expected as superior high-temperature semiconducting materials, for example, variable wide band-gap semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Because AlN has 2H structure and is soluble in 2H-SiC, AlN is possible to form solid solution with 2H-SiC. 20) In our previous study on SiC-AlN composites, the dissolution of AlN to SiC was revealed to facilitate phase transformation from 3C-to 2H-SiC. 21),22) Therefore, the peak of 2H phase observed in this work may indicate the existence of AlN remaining and/or SiC-AlN solid solution in the SiC bodies sintered with AlN additive.…”
Section: Resultsmentioning
confidence: 99%